A convergência de sujeito e objeto direto por uma sintaxe de bases enunciativas - Bruna Karla Pereira (2008)
According to studies of the enunciation, the organic and the symbolic domains of language govern the linguistic functioning. In this theoretical frame, we deal with the concepts of referential base (RB) and condensation of anchorage of syntactic places in order to analyze clauses of the Portuguese language, such as Ocorreram mudanças, in a wide and diversified corpus. On one side, RB is the semantic dimension of the clause, which remains steady even if we modify the verbal agreement or the NP position. On another side, verbs that act in the mentioned condensation are those ones which allow these kinds of modifications. In addition, they condense the anchorage of the syntactic places, subject and object, in one only field of reference. Concerning the concept of RB, we should consider the following clauses: (1a) Mudanças ocorreram, (1b) Ocorreram mudanças and (1c) Ocorreu mudanças. The three clauses keep on the same RB, even though the position of theNP or the verbal agreement were modified. On the other hand, in a clause, such as (2) O cão mordeu o funcionário, if the position of the NP is modified, for instance: O funcionário mordeu o cão, the RB of (2) is modified as well. Concerning the concept of condensation of reference, in (2), the anchorage of two syntactic categories, subject and object, takes place in two domains of reference named, respectively, o cão and o funcionário. In contrast, in (1), this anchorage is condensed, that is, it takes place in the same domain of reference named mudanças. As a result, in clauses such as (1), there is a convergence of subject and object in the same NP. The convergence is outlined by a spectrum where three strata stand out: group A (verbs that favour only clauses with convergence), group B (verbs that favour clauses with or without convergence) and group C (verbs that do not favour clauses with convergence). First, Ocorrer exemplifies A, because this verb does not allow clauses such as Eles ocorreram mudanças; second, morder exemplifies C, because this verb does not allow the variation in the position of the NP without affecting the RB; third, acabar exemplifies B, because this verb allows clauses which are condensatives (Acabou a festa) and clauses which are not (Acabei o trabalho). Therefore, B is an intermediate category that puts in relief the continuous aspect of this spectrum. In sum, the concepts of RB and condensation of reference settle the analysis of convergence. This analysis, in its turn, offers contributions to the study of the injunctions of the symbolic domain in the organic configuration of grammatical categories, since we recognize that subject and object are no longer represented as autonomous categories in the syntactic chain. On the contrary, they acquire visibility only in the symbolic domain of their constitution.